Analisis Perbedaan Kinerja Keuangan Sebelum Dan Sesudah IPO Pada Perusahaan Go Public Di BEI: Studi Kasus Pada Perusahaan Yang Menerbitkan IPO Pada Tahun 2019 - Dianita, Mirna; Niki Hadian; Prayitno, Yogo Heru (Politeknik Ganesha Medan, 2024)
Companies that carry out an IPO on the capital market will usually experience better performance changes and thus gain greater profits. Financial performance ratios are used by investors to make investment decisions in a company and determine company value. This research is in the form of comparative quantitative research. This comparative research aims to describe the differences in the financial ratio performance of companies conducting Initial Public Offerings (IPO) on the IDX before and after the IPO period. The population in this research is all companies listed in the IPO position on the Indonesia Stock Exchange (BEI) in 2019, a total of 55 companies with a sample of 40 companies. The research results show that there is no difference in financial performance in terms of Currnet Ratio (CR), Debt to Equity Ratio (DER) and Return on Equity (ROE) both before and after the IPO in non-financial sector companies that decided to IPO in 2019.